Penggunaan Deiksis pada Anak Usia 3-5 Tahun di Pemukiman TPA Antang Makassar (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study aims to describe the use of persona deixis, place deixis, and time deixis in children aged 3-5 years in Antang Landfill Settlement Makassar. This type of research is qualitative research. The data in the research is in the form of oral speech data in the form of words, phrases, clauses or sentences contained in the speech of children aged 3-5 years. The data collection technique is done through listening techniques, recording techniques, note-taking techniques, and transliteration. The result of the study reveals that the use of deixis in children aged 3-5 years in Antang Makassar landfill settlement includes three types of deixis namely persona deixis, place deixis, and time deixis. The use of persona deixis in children aged 3-5 years in Antang Makassar landfill settlement found first person singular deixis in the form of the word